The Role of SLAs in Xenotransplantation. Issue 2 (February 2021) - Ladowski, Joseph M.; Hara, Hidetaka; Cooper, David K.C.
Abstract : Advances in genetic engineering, particularly CRISPR/Cas9, have resulted in the development of a triple glycan-knockout (TKO) pig. There is minimal human antipig antibody binding to TKO pig cells. The TKO background has decreased antibody binding to a sufficiently low level that any additional xenoantigens expressed on the cells can now be more easily detected. One of these xenoantigens is the swine major histocompatibility complex, termed swine leukocyte antigens (SLA). SLA are the homolog to HLAs, a protein complex expressed on human tissue capable of stimulating the development of new antibodies in allotransplantation. These antibodies can result in graft failure through hyperacute, acute, or chronic rejection. Our knowledge of SLA, particularly in the last 5 years, has grown considerably. The presence, cause, and methods to detect anti-SLA antibodies will need to be carefully considered for the first clinical trial of xenotransplantation. The focus of this review is to summarize the role of SLA in xenotransplantation and consider whether it will prove to be a major barrier. Techniques are now available to mutate target SLA amino acids to ensure that cross-reactive anti-HLA antibodies no longer bind to SLA on the cells of the organ-source pigs. While deletion of SLA expression is possible, it would render the pig at risk for infectious complications. The ideal organ-source pig for HLA highly sensitized recipients may therefore be 1 with site-specific mutations to eliminate cross-reactive binding.